“Hark! I Hear the Cannons Roar”: Twenty years in the life of a “new tune” - Rouse, Andrew C. (FOCUS: Papers in English Literary and Cultural Studies, 2018)
In 1683 the Ottoman Turks were defeated at Vienna in what was to be a last serious bid to extend their empire further west, crushing the Habsburg dynasty as they did so. They had had good reason to believe the venture viable, as there existed no stable unity among the western powers. But for once the Holy League, a pan-European force comprising representatives from a variety of kingdoms, dukedoms and disinherited adventurers, cohered when it needed to do so and the several-century-long Ottoman threat essentially came to an end, or at least the beginning of the end. In the same year a street ballad appeared on the streets of London relating the defeat of the Turks at Vienna. A Carrouse to the Emperor, the Royal Pole, and the Much-Wrong’d Duke of Lorrain2 is a whimsical piece penned by the irrepressible Thomas D’Urfey that suggests that had the Islam religion permitted the Turkish soldiers to imbibe something stronger than coffee then the Ottoman host would have pressed on further, at least as far as the Rhine.